Electroencephalographic Correlate of Mexican Spanish Emotional Speech Processing in Autism Spectrum Disorder: To a Social Story and Robot-Based Intervention - Duville, Mathilde Marie; Alonso-Valerdi, Luz Maria; Ibarra-Zarate, David I. (Frontiers in Human Neuroscience, 2021)
Socio-emotional impairments are key symptoms of Autism Spectrum Disorders. This work proposes analyzing the neuronal activity related to the discrimination of emotional prosodies in autistic children (aged 9-11-year-old) as follows. Firstly, a database for single words uttered in Mexican Spanish by males, females and children will be created. Then optimal acoustic features for emotion classification will be extracted to further run a cubic kernel function Support Vector Machine algorithm in order to ascertain the speech corpus validity. As a result, human-specific acoustic properties of emotional voice signals will be identified. Secondly, those identified acoustic properties will be modified to generate stereotyped and simplified emotional utterances. Thirdly, both human and synthesized utterances will be used to study the electroencephalographic correlate of affective prosody processing in typically-developed and autistic children. Finally, and on the basis of the outcomes, synthesized voice-enhanced environments will be created to develop an intervention based on social-robot and Social StoryTM for autistic children to improve affective prosodies discrimination. This protocol has been registered at Biomedical Center under the following number: ISRCTN18117434.